2021
DOI: 10.1021/acsomega.1c01476
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Anion Control of the Partial Oxidation of Methane to Methanol on the β-PtO2Surface

Abstract: Although the C–H bond of methane is very strong, it can be easily dissociated on the (110) surface of β-PtO2. This is because a very stable Pt–C bond is formed between the coordinatively unsaturated Pt atom and CH3 on the surface. Owing to the stable nature of the Pt–C bond, CH3 is strongly bound to the surface. When it comes to methanol synthesis from methane, the Pt–C bond has to be cleaved to form a C–O bond during the reaction process. However, this is unlikely to occur on the β-PtO2 surface: The activatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 70 publications
0
9
0
Order By: Relevance
“…In recent years, it has been reported that reserves of methane-rich natural gas, such as tight gas, shale gas, and coalbed methane, are rapidly increasing . Much research has been conducted to convert methane into useful chemicals, such as light alkanes, olefins, alcohols, and aromatic compounds. Currently, indirect methods are most widely used for producing value-added products from methane: methane is partially oxidized or reformed to syngas (a mixture of CO and H 2 ), from which long-chain hydrocarbons and alcohols are produced by Fischer–Tropsch synthesis. , It would be of economic interest to evaluate the possibility of using natural gas as a feedstock for chemical synthesis . Direct conversion of methane to light hydrocarbons by oxidative or nonoxidative coupling of methane (OCM or NOCM) has a potential for more efficient one-step methane upgrading, avoiding the energy-intensive syngas generation stage. , The primary products of OCM and NOCM, C 2 species (i.e., ethane or ethylene), are precursors to a variety of higher value chemical products, such as plastics and resins .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, it has been reported that reserves of methane-rich natural gas, such as tight gas, shale gas, and coalbed methane, are rapidly increasing . Much research has been conducted to convert methane into useful chemicals, such as light alkanes, olefins, alcohols, and aromatic compounds. Currently, indirect methods are most widely used for producing value-added products from methane: methane is partially oxidized or reformed to syngas (a mixture of CO and H 2 ), from which long-chain hydrocarbons and alcohols are produced by Fischer–Tropsch synthesis. , It would be of economic interest to evaluate the possibility of using natural gas as a feedstock for chemical synthesis . Direct conversion of methane to light hydrocarbons by oxidative or nonoxidative coupling of methane (OCM or NOCM) has a potential for more efficient one-step methane upgrading, avoiding the energy-intensive syngas generation stage. , The primary products of OCM and NOCM, C 2 species (i.e., ethane or ethylene), are precursors to a variety of higher value chemical products, such as plastics and resins .…”
Section: Introductionmentioning
confidence: 99%
“…It can be inferred that for CH 3 OH* formation the catalytic activity follows the order of Cu−O−Ag/graphene (triplet) > Ag−O−Ag/graphene (triplet) > Ag−O−Ag/graphene (singlet) > Cu−O−Ag/graphene (singlet). Furthermore, Table3shows that Ag−O−Ag/graphene and Cu−Ag/graphene have lower reaction energies than some noble metal catalysts, such as Pt 2 O/ GO sheet (1.76 eV),66 N-doped β-PtO 2 (1.20 eV),65 and β-PtO 2 (2.08 eV) 65. And they are comparable with [Cu(μ-O)Cu] 2+ − ZSM-5,20,68 Pt 2 O 2 /GO sheet,66 Ni@C 24 N 24 ,69 and [Cu 3 (μ-O) 3 ] 2+ −MOR 70 catalysts.…”
mentioning
confidence: 99%
“…This step is considered to be the rate-limiting step of the whole reaction. Such a Mars-van Krevelen-type reaction mechanism for methanol formation was also studied for the b-PtO 2 and IrO 2 surfaces: 13 the activation barriers of the methyl group transfer on the b-PtO 2 and IrO 2 surfaces were calculated to be 47.9 and 60.6 kcal mol À1 , respectively, which are much higher than that on the a-PtO 2 surface.…”
mentioning
confidence: 99%
“…Note that the same process on the b-PtO 2 surface requires a larger desorption barrier of 26.1 kcal mol À1 . 13 With such a small methanol desorption barrier, methanol production is competitive with over-oxidation (Fig. S8, ESI †).…”
mentioning
confidence: 99%